Identification of CVID Patients With Defects in Immune Repertoire Formation or Specification - van Schouwenburg, Pauline A.; IJspeert, Hanna; Pico-Knijnenburg, Ingrid; Dalm, Virgil A. S. H.; van Hagen, P. Martin; van Zessen, David; Stubbs, Andrew P.; Patel, Smita Y.; van der Burg, Mirjam (Frontiers in Immunology, 2018)
.Common variable immune deficiency disorder (CVID) is the most clinically relevant cause of antibody failure. It is a highly heterogeneous disease with different underlying aetiologies. CVID has been associated with a quantitative B cell defect, however, little is known about the quality of B cells present. Here, we studied the naïve and antigen selected B-cell receptor (BCR) repertoire in 33 CVID patients using next generation sequencing, to investigate B cells quality. Analysis for each individual patient revealed whether they have a defect in immune repertoire formation (V(D)J recombination) or specification (somatic hypermutation, subclass distribution or selection). The naïve BCR repertoire was normal in most of the patients, although alterations in repertoire diversity and the junctions were found in a limited number of patients indicating possible defects in early B-cell development or V(D)J recombination in these patients. In contrast, major differences were found in the antigen selected BCR repertoire. Here, most patients (15/17) showed a reduced frequency of somatic hypermutation (SHM), changes in subclass distribution and/or minor alterations in antigen selection. Together these data show that in our CVID cohort only a small number of patients have a defect in formation of the naïve BCR repertoire, whereas the clear majority of patients have disturbances in their antigen selected repertoire, suggesting a defect in repertoire specification in the germinal centres of these patients. This highlights that CVID patients not only have a quantitative B cell defect, but that also the quality of, especially post germinal centre B cells, is impaired.